Solution of the Cauchy problem for system of the Euler-Poisson-Darboux equations - E. A. Maksimova (Vestnik Samarskogo Gosudarstvennogo Tehničeskogo Universiteta. Seriâ: Fiziko-Matematičeskie Nauki, 2011)
The system of Euler–Poisson–Darboux equations is considered, the Cauchy problem is solved for the case, when characteristic numbers of matrix–coefficient are complex conjugate and having real part in the interval (−1/2,0).